The inhibitory effects of Qingchang Wenzhong granule on the interactive network of inflammation, oxidative stress, and apoptosis in rats with dextran sulfate sodium‐induced colitis. Issue 6 (11th December 2018) - Shi, Lei; Dai, Yi; Jia, Boyi; Han, Yafei; Guo, Yi; Xie, Tianhong; Liu, Jiali; Tan, Xiang; Ding, Panghua; Li, Junxiang
Abstract: Background: Ulcerative colitis (UC) is a kind of complex immune disease, the pathogenesis of which remains elusive. Destruction of the intestinal barrier, extreme inflammation, oxidative stress, and apoptosis might play key roles in the development of UC. In previous studies, we observed that Qingchang Wenzhong granule (QCWZG) had the exact effect on the remission of UC in the clinic; however, the underlying mechanism has not been identified. This study aimed to reveal the effects of QCWZG on the intestinal physical barrier and the interactive network of inflammation, oxidative stress, and apoptosis in rats with dextran sulfate sodium (DSS)–induced colitis. Methods: Sixty rats were randomly divided into six groups: blank group, model group, high/mild/low‐dose QCWZG groups, and mesalazine group. The rats in the experimental group drank 4% DSS for 7 days and 1% DSS for the subsequent 7 days. Different medications or distilled water was supplied by intragastric administration for 7 days. The levels of colitis and indices related to inflammation, oxidative stress, and apoptosis were assessed. Results: Compared with the model group, the QCWZG group ( P  < 0.05) demonstrated attenuated disease activity index, colonic mucosa disease index, histological lesions, and colonic weights; lower levels of inflammatory substances, such as interleukin (IL)‐1α, IL‐6, tumor necrosis factor‐α, and myeloperoxidase; lower levels of malondialdehyde; and increased levels of superoxide dismutase and glutathione peroxidase. The QCWZG group also demonstrated elevated expression of Bcl‐2 and occluding but downregulated db expression of Bax and caspase 3 in the colon. Conclusion: QCWZG could relieve rats with DSS‐induced colitis from UC symptoms by improving the intestinal physical barrier, which resists the interactive network of inflammation, oxidative stress, apoptosis, and their overactivated interactions.